SUCCESSION INDICATIONS FROM VEGETATION IN TAILING DEPOSITION AREAS BASED ON VEGETATION PROFILE DIAGRAM - Windusari, Yuanita; Dahlan, Zulkifli; Hidayatullah, Hidayatullah (Indonesian Journal of Environmental Management and Sustainability, 2018)
One example of marginal land is land mined and sandy soil. This land tends to be difficult to overgrow vegetation. Environment 19 Mile is part of the ModADA or Ajkwa watershed that has been modified as a PTFI tailing deposition area. The effect of high natural erosion and transport of mineral soils during the tailings drainage process causes soil structure in ModADA, especially in the double dike area to form faster, and allow natural vegetation. Characteristics of succession in the area were observed by vegetation profiles. The combination of making transects and sampling plots was used as a method for observing characteristic vegetation in the double dike area. The results showed that based on differences in vegetation height and canopy area there were 3 layers of vegetation, namely A, B, and C in the Double levees with flooded or tend to dry area. In the flooded area, Paraserianthes afalcataria and Timonius timon were dominated by an average plant height of 17.33 m; and layer B is dominated by Pandanus lauterbachii with an average plant height of 6.83m. In areas that tend to be dry, layer A species is dominated by Timonius Timon, Ficus armiti Miq, Glochidion macrocarpa, and Sterculia sp with an average plant height of 14.75 m; while layer B is dominated by Casuarina equisetifolia, Ficus armiti King, Ficus armiti Miq, Glochidion macrocarpa, Antiaris sp, Macaranga aleuroitoides, and Campnosperma brevi petiolata with an average plant height of 8.39 m. Layer C is in both types of soil occupied by species Phragmites karka. The vegetation profile shows that the area is an area with double dikes in the early stages of succession. This proves that this region is able to develop into natural revegetation of ModADA and accelerated through reclamation